(untitled) (Damascus University Journal for engineering sciences, 2021)
The importance of this research comes from the study of important elements in Islamic architecture in general, and Serbian architecture in particular "stalactites" and the transition and transformation elements between surfaces, as such elements are architectural, structural, decorative and sculptural at the same time. The research aims to study the origin and evolution of these elements throughout history and analyze the multiple functions and the geometry of the parts forming such elements, and the unique aestheticism reflected by such elements on blocks and exterior and interior architectural surfaces carried out by different materials made up of those elements. The study also sheds light on biomimicry of these elements in their symbolism and features as plastic and abstract elements. In addition, the research studies architectural samples where architectural elements that come as development of stalactites have been used.